Are there differences between Entrepreneurial men and women? An insight in Opportunity Identification and Entrepreneurial Creativity. - Speelman, Anne-Martine (2010)
Men are more likely to be entrepreneurially active than women; this gender difference is currently underexplored within entrepreneurship academic literature. Within entrepreneurship the ability to identify business opportunities is believed to be one of the key competencies of successful entrepreneurs (Politis, 2005). Most authors recognise that creativity plays a part in opportunity identification and of wider entrepreneurial behaviour and is therefore seen as an important part of the entrepreneurial process (Barringer and Ireland, 2010; Hisrich, Peters and Shepherd, 2010; Mumford, 2000). Therefore the purpose of this dissertation is to look at gender differences in entrepreneurship by exploring the world view of six female entrepreneurs around the themes of opportunity identification, creativity and gender, and then to compare them against six male counterparts. Qualitative data for this research is gathered through conducting semi-structured interviews. This research noticed a slight difference in the use of identification processes between men and women. The main characteristics of the allocation, discovery and creative view from the economic school are all seen back in the results. However, in this small sample it is found that women tend to use the allocation and discovery processes and men do not use allocation, but the creative process view instead to identify opportunities. The difference in the use of processes is maybe a cause of the difference in experiential background between men and women (DeTienne and Chandler, 2007). Another finding in this research is that almost all entrepreneurs in this sample perceive themselves as creative. However, what makes entrepreneurs creative is not clear from this research. When exploring the interviews an extra topic became visible: entrepreneurial mothers make career and business choices with their family in mind. This may explain findings in the literature, that female entrepreneurial ventures tend to be smaller and grow at a slower rate (Deakins and Freel, 2009; Catley and Hamilton, 1998).